2004
DOI: 10.1590/s0004-27492004000200009
|View full text |Cite
|
Sign up to set email alerts
|

Projeto Mutirão de Catarata em centro de referência oftalmológico, em Pernambuco: perfil, grau de satisfação e benefício visual do usuário

Abstract: 6%). A freqüência dos parâmetros usados para avaliação do grau de satisfação dos usuários situou-se acima de 95,0%. Houve melhora estatisticamente significante da acuidade visual pós-operatória, em ambos os olhos. Olho direito -pré-operatória = X ± DP -0,193 ± 0,135 -pós-operatória = 0,650 ± 0,293, "t" = 13,469 -p < 0,0001. Olho esquerdo -pré-operatória = X ± DP -0,217 ± 0,197 -pós-operatória = 0,666 ± 0,301, "t" = 11,300 -p < 0,0001. Conclusões: A maioria dos pacientes incluídos no Projeto tinha baixa escolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(42 reference statements)
1
2
0
8
Order By: Relevance
“…The outcomes of this cross-sectional study of cataract patients indicated that those who presented to the referral hospital were younger and mainly females. This observation is similar to other Brazilian studies [ 11 13 ] and is likely due to the characteristics of the Brazilian population which has a greater number of elderly women (IBGE – 2010) [ 10 ]. Although the current study reported greater female presentation to the referral hospital, there was no statistical difference between genders ( p >0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The outcomes of this cross-sectional study of cataract patients indicated that those who presented to the referral hospital were younger and mainly females. This observation is similar to other Brazilian studies [ 11 13 ] and is likely due to the characteristics of the Brazilian population which has a greater number of elderly women (IBGE – 2010) [ 10 ]. Although the current study reported greater female presentation to the referral hospital, there was no statistical difference between genders ( p >0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Esses dados são semelhantes aos observados em outros estudos (10,(15)(16)(17) . Segundo censo demográfico de 2000 existe mais mulheres idosas do que homens idosos no Brasil (18) , o que também já foi evidenciado em estudos epidemiológicos, realizados em São Paulo e Pernambuco, com resultados de maior número de portadores de catarata no sexo feminino (10,17) . Os dados relativos à escolaridade e ocupação demonstraram que a maioria dos pacientes possuía escolaridade baixa e eram aposentados ou do lar, além de possuírem baixa renda familiar.…”
Section: Discussionunclassified
“…Isso demonstra o grau elevado de carência da população assistida pelos hospitais públicos, sendo estes economicamente inativos e com grande dificuldade de acesso a saúde. O mesmo resultado foi encontrado em estudos epidemiológicos feitos no estado de São Paulo e Pernambuco, mostrando que este problema possivelmente é vivenciado em todo o Brasil (10,17) . Observamos também que 57,4% dos pacientes chegaram ao nosso serviço com acuidade visual pior ou igual a 20/200 e 44% com acuidade visual pior ou igual que 20/400, demonstrando mais uma vez a provável demora no atendimento desses pacientes e todas as prováveis dificuldades que essa baixa visual avançada acarreta na vida dessas pessoas.…”
Section: Discussionunclassified
“…A similar profile (53.0% women) was found by Kara-José and Temporini in a study conducted in 5 urban areas in the state of São Paulo;¹ 67% were women in a large-scale cataract program in the state of Pernambuco, in 2002. 5 This predominance may be explained by the fact that in Brazil women have the role of caretakers of the family's health status.…”
Section: Discussionmentioning
confidence: 99%